Penguatan Karakter Qur'ani Melalui Literasi Al-Qur'an Dan Pendampingan Akademik Santri Syababul Khair - Muhtarom; Ongki Pranando; Dzulfikri Alifajri Dzul; Andini Alexa Saputri; Della Sintia Sari; Amanda Ramadhani (CV. Doki Course and Training, 2026)
The community service program through the Community Service Program (KKN) is one form of the implementation of the Tri Dharma of Higher Education in providing tangible contributions to society. This activity aims to improve the ability to read and understand the Qur'an and to instill Qur'anic character values in the younger generation at the RQ Syababul Khair Foundation.This study uses a descriptive qualitative approach with data collection techniques including observation, interviews, documentation, and literature study. The programs implemented include Qur'anic literacy development (tahsin, tahfidz, and muroja’ah), assistance in formal learning for children, development of the foundation’s profile website, and group exercise activities as part of community empowerment efforts. The results of the activities show an improvement in the students’ ability to read the Qur'an, increased learning motivation, and greater community participation in religious activities. In addition, the development of the foundation’s website helps expand public access to information. This program provides a positive contribution to forming a Qur'anic generation that has a good understanding of religion and possesses noble character.